2023
DOI: 10.1136/bmjpo-2022-001765
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a risk prediction model for medication administration errors among neonates in the neonatal intensive care unit: a study protocol

Abstract: IntroductionMedication administration errors (MAEs) are the most common type of medication error. Furthermore, they are more common among neonates as compared with adults. MAEs can result in severe patient harm, subsequently causing a significant economic burden to the healthcare system. Targeting and prioritising neonates at high risk of MAEs is crucial in reducing MAEs. To the best of our knowledge, there is no predictive risk score available for the identification of neonates at risk of MAEs. Therefore, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The comprehensive details of the data collection procedure are outlined in our published protocol for the development and validation of a risk prediction tool aimed at identifying neonates at risk of MAEs [ 24 ]. In summary, the flowchart for the direct observational study is shown below ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The comprehensive details of the data collection procedure are outlined in our published protocol for the development and validation of a risk prediction tool aimed at identifying neonates at risk of MAEs [ 24 ]. In summary, the flowchart for the direct observational study is shown below ( Fig 1 ).…”
Section: Methodsmentioning
confidence: 99%